2023
DOI: 10.3390/nano13050808
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement by Hybrid Nano Additives—Graphene Nanoplatelets/Cellulose Nanocrystal for the Automobile Cooling System (Radiator)

Abstract: A radiator is used to remove a portion of the heat generated by a vehicle engine. It is challenging to efficiently maintain the heat transfer in an automotive cooling system even though both internal and external systems need enough time to keep pace with catching up with evolving engine technology advancements. The effectiveness of a unique hybrid’s heat transfer nanofluid was investigated in this study. The hybrid nanofluid was mainly composed of graphene nanoplatelets (GnP), and cellulose nanocrystals (CNC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The study shows that graphene nanocoolant enhances the heat transfer rate of radiator by 68% [22]. In another experimental study which investigated the automobile cooling system suspended with GnP and cellulose nanocrystals (CNC) nanoparticles, Yaw et al, [23] reported that the presence of GnP and CNC nanoparticles intensifies the convective heat transfer coefficient of radiator by 51.9%. Similar enhancement rate is also reported by Selvam et al, [24] which showed that GnP-EG/water nanofluid increases the convection heat transfer coefficient of automotive radiator by 51% [24].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The study shows that graphene nanocoolant enhances the heat transfer rate of radiator by 68% [22]. In another experimental study which investigated the automobile cooling system suspended with GnP and cellulose nanocrystals (CNC) nanoparticles, Yaw et al, [23] reported that the presence of GnP and CNC nanoparticles intensifies the convective heat transfer coefficient of radiator by 51.9%. Similar enhancement rate is also reported by Selvam et al, [24] which showed that GnP-EG/water nanofluid increases the convection heat transfer coefficient of automotive radiator by 51% [24].…”
Section: Introductionmentioning
confidence: 96%
“…In the up-to-date literature, most of the studies on graphene-based nanofluid flow in automotive radiator employ the mixture of water and EG as the basefluids [22][23][24][25]. Numerical investigations on the convective performance of water-based GnP nanofluids in radiator for improving the cooling of automotive engine is relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Many cooling systems used in industries and automobiles are currently struggling with this problem. Utilizing traditional cooling agents like water, motor oils, and optoelectronic systems, various industries including air-conditioning, power generation, and chemical processes employ ethylene glycolprocessing instruments, mineral oil, and other sectors [3]. Unfortunately, it has been discovered that conventional coolants like engine oil and ethylene glycol are not as efficient as desired.…”
Section: Introductionmentioning
confidence: 99%
“…However, nanofluids, composed of nanoparticles dispersed in base fluids like ethylene glycol and water, offer improved thermal conductivity and stability compared to traditional cooling agents [4,19,20]. Research shows that nanofluids provide heightened conductivity and enhanced thermal stability, making them a promising alternative for various heat transfer applications [21][22][23]. Nonetheless, utilizing nanofluids in cooling systems presents challenges, as solid particles within the fluid can lead to corrosion and erosion of pipe surfaces, raising concerns about the impact of nanocoolants on metal degradation rates [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%